1983
DOI: 10.1016/0022-4073(83)90127-9
|View full text |Cite
|
Sign up to set email alerts
|

Oscillator strengths of neutral and singly ionised molybdenum

Abstract: Abstract--Oscillator strengths of 174 Mo(I) and 58 Mo(II) lines in the range 247~5570 A were obtained from wall-stabilised arc and hollow cathode measurements. Sets of relative f-values were determined by a combination of hook and emission measurements requiring no assumptions concerning the plasma state. The sets have been enlarged considerably by evaluating spectra recorded with a Fourier spectrometer. The relative Mo(I)f-values were converted to an absolute scale by means of radiative lifetimes measured by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

1984
1984
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 9 publications
2
27
0
Order By: Relevance
“…The CP2 lifetimes are definitely too long in Re ii and Mo i . In these two species, the CP1 core‐polarization model reproduces reasonably well our laser LIF measurements and those of Kwiatkowski et al (1981) and Schnehage et al (1983). In Tc ii , our CA calculations support also the CP1 lifetimes.…”
Section: Discussion Of the Resultssupporting
confidence: 79%
See 2 more Smart Citations
“…The CP2 lifetimes are definitely too long in Re ii and Mo i . In these two species, the CP1 core‐polarization model reproduces reasonably well our laser LIF measurements and those of Kwiatkowski et al (1981) and Schnehage et al (1983). In Tc ii , our CA calculations support also the CP1 lifetimes.…”
Section: Discussion Of the Resultssupporting
confidence: 79%
“…g LIF (Kwiatkowski et al 1981). h LIF measurements of Zimmermann et al reported as a private communication by Schnehage et al (1983).…”
Section: Computational Strategymentioning
confidence: 97%
See 1 more Smart Citation
“…The first results were the arc measurements of Corliss and Bozman (1962), but these results are now known to be affected by large systematic errors and they have been superseded by more recent data. Schnehage et al (1983) determined relative f -values for 174 Mo I and 58 Mo II transitions in the range 24.7-557.0 nm from wall-stabilized arc and hollow cathode measurements. The Mo I data were normalized to an absolute scale using four experimental lifetime values from Kwiatkowski et al (1981).…”
Section: Introductionmentioning
confidence: 99%
“…Transition probabilities for 570 Mo I lines in the range of 294.4-976.7 nm belonging to 56 levels with an energy range of 25; 614-42; 345 cm −1 were deduced from combining experimental lifetimes and their branching fractions by Whaling et al [9]. Oscillator strengths of 174 Mo I lines ranging from 247 to 557 nm were obtained from wall-stabilized arc and hollow cathode measurements by Schnehage et al [10].…”
Section: Introductionmentioning
confidence: 99%